The unbeatable Squirrel Girl. Vol. 10, Life is too short, Squirrel - North, Ryan, 1980- (Marvel Worldwide, 2019)
A collection of graphic novel stories featuring the adventures of Squirrel Girl who battles the Grim Reaper, goes one-on-one with Iron Man, embarks on an underwater adventure, fights an invasion of Skrulls, and encounters Spider-Man.